The associations of Tibetan Plateau spring snow cover with East Asian summer monsoon rainfall before and after 1990 - Wijngaard, René Reijer; Oh, Hyoeun; Khanal, Sonu; Yoon, Arim; van de Berg, Willem Jan; An, Soon-Il (Frontiers in Earth Science, 2024)
In recent decades, the existence of a relationship between snow cover on the Tibetan Plateau (TP) and East Asian summer monsoon (EASM) rainfall has been emphasized. According to recently published studies this snow-monsoon relationship experienced a shift after 1990. Although the changing snow-monsoon relationship has been studied, the causes of the interdecadal changes remain unclear. This study assesses the associations of TP spring snow cover with EASM rainfall before and after 1990 and explores what possible mechanisms could be responsible for the interdecadal changes. Correlation and composite analyses were used to assess the strength of the relationship between TP spring snow cover and EASM rainfall and to analyze the atmospheric and land surface patterns associated with high snow cover. The outcomes suggest that the relationship between TP spring snow cover and EASM rainfall changes from partially negative to positive over all regions of the TP from 1968–1990 (P1) to 1991–2019 (P2), implying that more snow cover is associated with less (more) EASM rainfall during P1 (P2). In P1, years with high snow cover are associated with an anomalous cyclone southwest of the TP (positioned over Iran and Pakistan) in spring, which persists into the following summer, partly due to the underlying snow cover. The anomalous cyclone is accompanied by downstream anomalies over East Asia, which form a strong east-west oriented wave pattern and induce a northerly inflow of dry air over East Asia, reducing rainfall over the northern EASM domain. In P2, high snow cover years are associated with an anomalous cyclone over the western TP, which weakens and loses its significance in May-June and summer, partly due to a decline in snow forcing. Southeastward propagation of wave energy in May-June initiates the formation of an anomalous anticyclone over southeastern China and the western North Pacific. Concurrently, a meridional circulation develops over East Asia that enhances the southwesterly moisture inflow, resulting in increased EASM rainfall. The changing snow-monsoon relationship can be linked to different wave train patterns resulting from changes in the background zonal wind and meridional temperature gradients. This research contributes to a better understanding of the changing snow-monsoon relationship.